DRAM circuit design : (Wiley-Interscience, 2008)
Dynamic Random Access Memory (DRAM) technology has been one of the greatestdriving forces in the advancement of solid-state technology. With its ability to produce high product volumes and low pricing, it forces solid-state memory manufacturers to work aggressively to cut costs while maintaining, if not increasing, their market share. As a result, the state of the art continues to advance owing to the tremendous pressure to get more memory chips from each silicon wafer, primarily through process scaling and clever design